Navigating Indonesia-United States relations, 1967-1969 - Shannon Smith (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2023)
Individuals not holding formal positions are often overlooked in studies of international relations, where the focus is generally on Heads of State, foreign ministers and accredited professionals attached to diplomatic services. Indeed, it is an anomaly for an individual, and certainly a non-national, to act as an envoy for one government, and for that intermediary to be attached great importance by another foreign government. Such an abnormality was Clive Williams, President Soeharto of Indonesia’s Australian Whisperer. Williams has never been mentioned in a single diplomatic, political or historical account of United States-Indonesia relations. But as shall be seen, he was an extremely effective and indispensable intermediary for both countries as they moved towards closer relations in the late 1960s. The practice of a non-national assisting a national leader in international affairs is a fascinating concept.